Digestão do feno Tifton 85 (Cynodon sp.) sob níveis de suplementação energética e suplementação nitrogenada - Netto, Diego Peres (2006)
The experiment was conducted to evaluate the intake, digestibility, ruminal fermentation, nitrogen retention (N) and ruminal microbial protein synthesis in lambs fed tifton 85 (Cynodon sp.) hay or hay supplemented with urea and levels (0, 5, 10 and 15 g/kg of the live weight (PV)) of cassava meal. Ten castrated cross breed lambs Texel X Corriedale (mean LW of 30±1kg), housed in metabolic cages, were used in a double 5X5 Latin Square experiment. Cassava meal supplementation increased, linearly (P<0,01), the intake of non nitrogenous compounds and energy, with exception of total neutral detergent fibre intake (CFDNt), as well as hay components (MS, MO, FDN) and digestibility of the FDN, that decreased linearly (P<0,01). The intake of nitrogenous compounds increased linearly (P<0,01), with exception of the intake of N of the hay that decreased linearly (P<0,01), with offers of cassava meal. The urinary N excretion (NU) and efficiency of the microbial protein synthesis were similar among treatments (P>0,05). Mean ruminal pH values and ammonia N concentrations decreased linearly (P<0,01), but, the sugars concentrations and peptídeos increased linearly (P<0,01) with level of cassava meal supplementation, the amino acids concentrations were quadratically related (P<0,05) to cassava meal level. It was expected, at least at the initial level of energy supplementation an additive effect on food intake and hay intake as a result of a possible increment of the ruminal degradation of the FDN of hay. Nevertheless, this trend was not confirmed, therefore it occurred an additive linear effect on the intake of the MO, a linear substitutive effect on the hay intake and a negative effect on the fibre digestibility. Although it increases the offers total of nutrients, the energy supplementation diminishes the use of the hay for the animals.